Biosimilars - drugs of the future - E. A. Eltcova; G. V. Ramenskaya; E. A. Smolyarchuk; A. V. Bushmanova (Фармакокинетика и Фармакодинамика)
The article describes the basic terms and definitions relating to biosimilars, generics and original drugs. Also described a brief history of the origin and development of the biotechnology industry and drugs produced using biological objects. The main difference between biosimilars and generics, as well as their differences to innovative medicines. The process of biotechnological production, and main applications of biosimilars. It analyzed the legal framework of the Russian Federation and the European Union.